An Overview of Antihypertensive Combination Therapy Among Patients in the Referral Back Program at the UPTD Puskesmas Kuala Pembuang II, 2025 - Nurliani Nurliani; Sri Wahyuni (JOURNAL SAINS STUDENT RESEARCH, 2026)
Background: Hypertension is a chronic disease with high prevalence requiring continuous management to prevent cardiovascular complications. The Referral Back Program (PRB) facilitates routine medication services for stabel hypertensive patients at primary health care facilities. Objective: This study aimed to identify the demographic characteristics of hypertensive patients and describe the pattern of combination antihypertensive therapy among PRB patients at UPTD Puskesmas Kuala Pembuang II in 2025. Methods: A descriptive non-experimental study with a quantitative approach was conducted using retrospective data from the PRB register. The total sample consisted of 170 hypertensive patients. Results: Most patients were female and belonged to the 55-64 years age group. Combination therapy was used more frequently than monotherapy, with the Amlodipine and Candesartan combination being the most commonly prescribed regimen. The most frequently used single therapies were Amlodipine and Candesartan. Conclusion: Combination antihypertensive therapy was more predominantly used than monotherapy among PRB patients at UPTD Puskesmas Kuala Pembuang II, with patients predominantly female and in the older age group.